2020
DOI: 10.4103/1735-3327.292069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deep cryogenic treatment on cyclic fatigue resistance of controlled memory wire nickel-titanium rotary instruments

Abstract: Background: Cryogenic methods have been used to increase the wear, abrasion, corrosion resistance and to improve the strength of metals. The aim of this study was to evaluate the effect of cryogenic treatment on the cyclic fatigue resistance of rotary nickel-titanium (NiTi) instruments. Materials and Methods: In this in vitro study, 20 Hyflex (Coltene, Altstätten, Switzerland) nickel-titanium instruments, size 25, 0.06 taper, were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
6
2
2
Order By: Relevance
“…Similarly, Vinothkumar et al [ 147 ] demonstrated that dry CryoT drastically increased the cyclic fatigue resistance by 13%. This contrasts with more recent studies that found no improvement in cyclic fatigue resistance in NiTi rotary instruments after cryogenic treatment [ 148 , 149 ]. Differences in methodology likely explains the contrasting results.…”
Section: Metallurgy Of Nickel–titanium Alloycontrasting
confidence: 86%
See 1 more Smart Citation
“…Similarly, Vinothkumar et al [ 147 ] demonstrated that dry CryoT drastically increased the cyclic fatigue resistance by 13%. This contrasts with more recent studies that found no improvement in cyclic fatigue resistance in NiTi rotary instruments after cryogenic treatment [ 148 , 149 ]. Differences in methodology likely explains the contrasting results.…”
Section: Metallurgy Of Nickel–titanium Alloycontrasting
confidence: 86%
“…Differences in methodology likely explains the contrasting results. Yazdizadeh et al [ 149 ] and Sabet et al [ 148 ] used a wet CryoT technique and measured cyclic fatigue using a static model which is not reflective of clinical practice.…”
Section: Metallurgy Of Nickel–titanium Alloymentioning
confidence: 99%
“…Glavne uzroke preloma instrumenata predstavljaju torziono opterećenje i ciklični zamor [7,8,9]. U slučaju kada je vrh turpije zaglavljen u kanalu tokom rotacije instrumenta, kada se deo instrumenta uvije u zid kanala, kada je vrh instrumenta veći od promera kanala korena, ili kada se vrši prekomerni pritisak na instrument u toku rada, dolazi do preloma instrumenta usled torzionog opterećenja [10,11]. Mnogo češći uzrok preloma instumenata je ciklični zamor koji nastaje usled neprekidnog smenjivanja kompresije i istezanja u svakoj tački savijenog instrumenta u predelu krivine kanala.…”
Section: Uvodunclassified
“…The main causes of instrument breakage are torsional load and cyclic fatigue [7,8,9]. In the case when the tip of the file is stuck in the canal during the rotation of the instrument or part of the instrument is twisted into the wall of the canal, the tip of the instrument is larger than the diameter of the root canal or when excessive pressure is applied to the instrument during operation, the instrument breaks due to torsion loads [10,11]. A much more common cause of broken instruments is cyclic fatigue that occurs due to the continuous alternating compression and stretching at each point of bent instrument in the region of the canal curvature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation